Three-dimensional simulation of gas-solid flow in a fluidised bed with flexible ribbon particles. (March 2020) - Wu, Kai; Zhang, Erqiang; Xu, Ji; Yuan, Zhulin; Zhu, Wenkui; Li, Bin; Wang, Le; Luo, Dengshan
Highlights: A flexible ribbon chain model and a modified drag force are used. The spring constants are proposed and validated reasonably. Dynamic behaviour of the flexible ribbon particles is vividly investigated. Abstract: Fluidisation is a widely used process in the industry as it offers high solid-gas contact efficiency and high heat and mass transfer, hence making it the unit operation of choice for drying. For instance, in the tobacco industry, drying of cut-tobacco is usually performed in fluidised beds. Unlike other particle materials, cut-tobacco exhibit ribbon-like morphology and are highly flexible. The high tendency of such particles to intertwine and form clusters could significantly influence the hydrodynamic characteristics and equipment performance. Therefore, it is of great significance to understand the dynamic behaviours of flexible ribbon particles in the fluidised bed. However, reported studies on such particles in the literature are scarce, and there is no large-scale numerical calculation for that matter. In this paper, the dynamic behaviours of flexible ribbon particles in a fluidised bed are investigated numerically using a two-way coupling of Discrete Element Method (DEM) and Computational fluid dynamics (CFD). A flexible ribbon chain model is used. The spring force constants is proposed and validated reasonably. Compared to other models, the flexible ribbon particle model provides better flexibility. It could also accurately reflect the flow properties of flexible ribbon particles to a certain extent. The effects of particle mass flow rate, superficial gas velocity and other process parameters on the particle dynamics in a fluidised bed are thoroughly studied in this paper. The numerical simulations are validated with experimental data, and the results show a very good agreement. Graphical abstract: Image, graphical abstract